Sobre a base física da assimetria causal: um estudo de abordagens reducionistas - Felipe Torres Candido (2019)
The second half of twentieth century is marked by an intense debate about causation. One of the main problems in this debate is the need to determine a correspondent in the physical world or in the laws of physics to causal asymmetry. Thus, the present work intends to outline some of the main reductionist perspectives of the causal asymmetry of the twentieth century, aiming to clarify the main problems in these perspectives and trying to provide perspectives for the continuity of the debate. First, we deal with the problem visualized by Bertrand Russell about the incompatibility between causal asymmetry and the symmetry of the Laws of Physics. Then, we show how Hans Reichenbach tries to remedy the problem with his robust theory that he intended to reduce causation to entropy. Soon after, we approach the debate that takes place after Reichenbach's ideas that begins with the counterfactual theory of David Lewis and culminates in the criticisms received by all the reductionist programs presented. Finally, we discuss how some attempts to solve the criticisms made especially to Lewis and Reichenbach culminate in a macroscopic perspective of causation, and the immediate implications of such a perspective.